Reporting of physical activity levels in intensive care unit survivors - Sakshi Surve; Mukesh Kumar Sinha; Vishal Shanbhag; G. Arun Maiya (Scientific Reports)
Abstract The primary aim of this study was to report the physical activity profiles and the functional status of critically ill patients at one-month post-discharge using the ‘Physical Activity Scale for the Elderly (PASE)’ questionnaire. Study participants included were between 45 and 75 years of age, admitted to ICUs for a minimum of 24 h. Altogether, 110 study participants were included by consecutive sampling, from which six were lost to follow up. This prospective observational study was carried out in the ICU settings of Kasturba Hospital, Manipal. All the participants were assessed for ICU-acquired weakness at ICU discharge and were later followed up after one month for their physical activity level via telephonic follow-up. Participants’ mean age was 57.5 ± 9.82 years, out of which 71% were female. The prevalence of ICU-acquired weakness was found to be 80% in these participants. The median PASE score was 5 (2–27) at one-month follow-up among the participants. Medical Research Council (MRC) sum score showed a statistically significant positive moderate association with PASE score (‘r = 0.70, p < 0.05). The study showed that about 97.1% of ICU survivors lead a sedentary lifestyle and showed alarmingly high levels of physical inactivity at one month post-hospital discharge.